The Female Menstrual Cycles Effect on Strength and Power Parameters in High-Level Female Team Athletes - Dasa, Marcus S.; Kristoffersen, Morten; Ersvær, Elisabeth; Bovim, Lars Peder; Bjørkhaug, Lise; Moe-Nilssen, Rolf; Sagen, Jørn V.; Haukenes, Inger (Frontiers in Physiology, 2021)
Purpose: The female menstrual cycle is characterized by hormonal fluctuations throughout its different phases. However, research regarding its effect on athletic performance in high level athletes is sparse. The aim of this study was to investigate the female menstrual cycles effect on strength and power performance in highly trained female team athletes. Methods: 35 athletes (Age 21.17 ± 3.3 years; weight 65.6 ± 8.7 kg; height 170.2 ± 8 cm; fat free mass 52.3 ± 7.1) completed the study after a six-week testing period. Participants were recruited from the team sports soccer, handball and volleyball. Testing protocol consisted of maximal voluntary isometric grip strength, 20-meter sprint, countermovement jump and pneumatic leg-press. Based on self-reported use of hormonal contraceptives, participants were divided into non-hormonal contraceptive group and hormonal contraceptive group, the latter working as a control group. Menstrual cycle phase was confirmed by serum hormonal analyses in venous blood samples in the non-hormonal contraceptive group. Results: There was no significant difference between groups during the menstrual cycle for any of the outcome variables, maximal voluntary isometric grip strength F (3.29) = 0.362; 20-meter sprint F (3.24) =0.710; countermovement jump F (3.26) = 2.361; leg-press F (3.26) = 1.746. Conclusion: In high level female team athletes, no difference in performance was observed based on hormonal contraceptive status. This suggest that the menstrual cycle does not alter strength and power performance on a group level in high level team athletes.